1990
DOI: 10.1172/jci114868
|View full text |Cite
|
Sign up to set email alerts
|

Elevated insulin receptor content in human breast cancer.

Abstract: Univariant analysis revealed that the insulin receptor content of the tumors correlated positively with tumor size (P = 0.014), histological grading (P = 0.030), and the estrogen receptor content (P = 0.035). There were no significant correlations between insulin receptor content and the age, body weight, menopausal status, and nodal involvement of the patients. These studies indicate, therefore, that the insulin receptor content is increased in breast cancers and raise the possibility that the insulin recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
185
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(196 citation statements)
references
References 26 publications
7
185
1
3
Order By: Relevance
“…In a case-control investigation on subclinical diabetes, hyperinsulinaemia with insulin resistance was a significant risk factor for breast cancer, independent of weight or body fat distribution (Bruning et al, 1992). Hyperinsulinaemia, as in late-onset diabetes, may promote breast cancer, as insulin is an important growth factor for human breast cancer cells (Freiss et al, 1990) and elevated insulin receptor contents have been found in breast cancer specimens (Papa et al, 1990). Furthermore, insulin levels are inversely related to SHBG levels and, thus, positively related to available oestrogens and androgens.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control investigation on subclinical diabetes, hyperinsulinaemia with insulin resistance was a significant risk factor for breast cancer, independent of weight or body fat distribution (Bruning et al, 1992). Hyperinsulinaemia, as in late-onset diabetes, may promote breast cancer, as insulin is an important growth factor for human breast cancer cells (Freiss et al, 1990) and elevated insulin receptor contents have been found in breast cancer specimens (Papa et al, 1990). Furthermore, insulin levels are inversely related to SHBG levels and, thus, positively related to available oestrogens and androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of insulin have been related to increased risk of breast cancer and mortality from it (47) and colon cancer (48). It has been shown that human breast cancer specimens have higher IR content than normal breast tissue and fibroadenoma specimens (49). Increasing evidence also suggests that, in breast cancers, there is higher expression of IR-A (14, 17).…”
Section: Is Ir Also a Target For Cancer Therapy?mentioning
confidence: 99%
“…The insulin receptor (IR) is overexpressed both in breast cancer cells in culture, and in most human breast cancer specimens (Milazzo et al, 1992a;Papa et al, 1990). Insulin, via its own receptor, stimulates growth and metabolism in breast cancer cells (Milazzo et al, 1992a;Papa et al, 1990;Papa and Bel®ore, 1996;Dickson and Lippman, 1995), and when the IR is overexpressed in NIH3T3 or normal breast cells a ligand-dependent malignant phenotype is induced (Giorgino et al, 1991;Frittitta et al, 1995).…”
Section: Introductionmentioning
confidence: 99%